Evaluation of dermatologic diagnostic ability on skin of colour in preclinical medical students - Adina Greene; Tara Ghalambor; Scott Penner; Chase Irwin; K. Taraszka Hastings (Skin Health and Disease)
Abstract Background Various studies have revealed that there is a disproportionately low representation of skin of colour (SOC) in medical school dermatologic curriculum and board study resources. Methods First‐year and second‐year medical students were emailed an 18‐question survey regarding (1) identifying correct diagnoses of dermatologic conditions on either White skin or SOC and (2) their confidence in identifying dermatologic conditions on SOC. Results 15% of the images of dermatologic conditions included in the institutional preclinical curriculum show images of patients with SOC. Regarding overall scores for diagnosing dermatologic diseases, students performed similarly on both the White image survey (61.73%) and SOC image survey (66.20%) with no statistically significant differences between surveys (p = 0.14). Second‐year medical students performed better than first‐year medical students overall (p = 0.01) and on White skin image survey scores (p = 0.02) but not on people of colour image survey scores (p = 0.09). Students largely agreed that they were more comfortable identifying dermatologic diagnoses on White skin and that their school could benefit from increased SOC dermatological resources. Conclusion The overall low scores for the diagnosis of common skin conditions on both the White image and SOC image survey by first‐ and second‐year students are not surprising given the results of a prior study and support the need for re‐exposure to dermatology presentations in all skin types during the preclinical curriculum. The low scores support the need for changes in the pre‐clinical dermatology curriculum to improve diagnostic ability. Second‐year students performed better at diagnosing dermatologic conditions overall and on White skin compared to SOC at the end of their didactic years, possibly due to an underrepresentation of SOC images in institutional and outside educational resources. Attitudes towards school‐specific dermatologic SOC education demonstrated a clear desire amongst students for more exposure to dermatologic conditions in various skin colours throughout the curriculum.